Quantitative 3D-CT imaging of sarcopenia mitigation in elderly: evidence from a case report - Marco Quadrelli; Tommaso Baccaglini; Aldo Morra (PAGEPress Publications, 2024)
This case study examines the effectiveness of using combined CT imaging and 3D imaging in monitoring the prevention of sarcopenia through continuous daily exercises in an elderly patient. Using a 256-slice CT scanner with dose reduction technology and advanced muscle segmentation with the open-source software DAFNE, we compared changes in muscle mass and density in a 70-year-old patient in 2014 and in 2023. The obtained images allowed the creation of detailed 3D models for a more accurate and intuitive assessment of the leg musculature. Despite aging, the results of the scans performed at the beginning and end of the study period did not show significant changes in the patient's musculature, suggesting that a persistent Full-Body in-Bed Gym protocol ("Gym Bed" exercise routine) can effectively contribute to maintaining muscle mass and density in the elderly. These preliminary results highlight the potential of advanced imaging techniques not only to diagnose but also to quantify the effectiveness of non-pharmacological interventions against sarcopenia.